Woman’s resistance against discrimination in Stacey Lee’s The Downstairs Girl - Indri Satya Handayani; Ni Made Widisanti Swetasurya; Dyah Kristyowati (Universitas Pakuan, 2025)
This research focuses on the main character's resistance to discrimination in the novel The Downstairs Girl by Stacey Lee. The study aims to highlight the gender and racial discrimination experienced by the main character and her resistance to this discrimination. This study utilized a descriptive analysis method, incorporating intrinsic elements such as character, characterization, conflict, setting, and symbols, and extrinsic elements including discrimination and resistance theory. This study utilized library research techniques, specifically examining, and researching literature in novels. The findings revealed that resistance to discrimination can be manifested through both overt and subtle actions, whether openly or discreetly. In summary, the protagonist, Jo Kuan, faced gender discrimination in the form of violations of women's rights, as well as racial discrimination through restrictions and exclusion. These challenges prompted the main character to demonstrate bravery and resilience in resisting oppression.Keywords: Discrimination; Resistance; Gender; Racial